(untitled) (Muse, 2025)
The so-called Dante Estense (Ms. It. 474 = alfa.R.4.8, Biblioteca Estense Universitaria di Modena) is unique among illuminated manuscripts of the Divine Comedy. Created between the end of the 14th and the beginning of the 15th century, it stands out for the breadth and coherence of its illustrative cycle: two hundred and seventy-one watercolour drawings, systematically placed in the upper margin of each folio, create a continuous visual narrative parallel to Dante’s text. The Paradiso is particularly original, characterised by a rich musical and choreographic iconography featuring a continuous procession of dancing angels and musicians accompanying Dante’s ascent. The intertwining of dance and music, structured in two articulated, interdependent and specular sections, creates a refined visual counterpoint that reflects the tension between movement and contemplation, an essential feature of the third Canticle. Its fidelity to the text, the originality of its iconographic choices and the centrality of its performative dimension make Dante Estense an exceptional example of Dante’s figurative reception, in which words, images and performance merge to produce one of the most evocative and complete interpretations of the poem.